The mechanical properties and stiffness of aorta in obese children - Şen, Hakan; Bakiler, Ali Rahmi; Aydoğdu, Süleyman Ayvaz; Ünüvar, Tolga; Yenisey, Çiğdem; Arun Özer, Esra (The Turkish Journal of Pediatrics, 2013)
Obesity in children has also been associated with the development of early cardiovascular abnormalities. The aim of this study was to investigate the relationship between aortic stiffness and some risk factors in obese children. Sixty obese children and 60 age- and sex-matched healthy controls were assessed. The mechanical property parameters were measured or computed: lumen diastolic and systolic diameters, aortic strain and elastic modules. Compared to controls, obese children had altered stiffness values of the aorta, whereas strain was not different. Compared to controls, obese children had higher systolic and diastolic blood pressure values. Insulin level, homeostasis model assessment (HOMA) score, and total cholesterol, triglycerides, lowdensity lipoprotein (LDL), and leptin levels were significantly higher, while adiponectin, high-density lipoprotein (HDL) levels and quantitative insulin sensitivity check index (QUICKI) scores were significantly lower in obese children than in controls. Obesity in children increases aortic stiffness, which suggests that the joint effect of insulin resistance, serum leptin and adipokine levels and obesity can have a considerable impact on preclinical arterial changes and could play an important role in the early pathophysiology of macrovascular disease.